Pengaruh Luas Penampang Wadah Terhadap Besarnya Reduksi Volume Sampah Organik Rumah Tangga Menggunakan Larva Lalat Bsf (Black Soldier Fly) - Bayu Chondro Purnomo; Nurjazuli Nurjazuli; Suhartono Suhartono (Jurnal Sehat Mandiri, 2021)
This research is Quasi experimental with the Post Only Group Design method. This study uses the amount of maggot and organic waste with a ratio of 1: 2, with 1/2 kg of maggot against 1 kg of garbage, with a volume of 6000 cm3 containers and a variation of the cross sectional variation of 20x20 cm2 with a height of 15 cm, the cross section area of ​​30x20 cm2 with a height of 10 cm and 10 cm and the cross section area of 30x40 cm2 with a height of 5 cm. Based on the results of the research that has been made, the waste reduction by BSF larvae, the cross-sectional area of ​​20x20 cm was 516.7 gr, the cross-sectional area of ​​30x20 cm was 555.6 gr, while the cross-section area of ​​30x40 cm was 644.4 gr. The highest reduction is obtained from the cross-sectional area of ​​30x40 cm. Based on the results of the normality test it obtained the value of P-Value> α (0.05). This indicates that the data is distributed normally by looking at the variant difference test, obtained a value of p-value 0.049 (<α). Then it can be concluded that there is an influence between cross-sectional area and waste reduction by BSF larvae. The wider cross-section of the garbage container, the easier BSF larvae reduce organic waste.